Analisis Gangguan Fonologi Pada Mustofa Dalam Podcast Wkwk Project By Genflik - Helmi Seftiani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Language is the primary tool humans use to convey thoughts and messages, both verbally and in writing. According to experts, language is a system of sound symbols used for communication and interaction, consisting of phonology, lexicon, and grammar. Phonology studies the sounds of language and is a crucial aspect of linguistics, divided into phonetics and phonemics. Language plays an important role in daily life, not only as a communication tool but also as a reflection of individual or group identity. Language preserves cultural heritage and strengthens social relationships within a community. Proper use of language facilitates communication and influences the understanding of the interlocutor. The development of globalization makes language a means of cross-cultural connection, aiding in collaboration and participation between countries. However, every language faces challenges in pronunciation, word formation, writing, and sentence usage. Phonological disorders, such as in individuals with cleft lip and stuttering, affect speaking ability and language comprehension. A cleft lip causes difficulties in producing certain consonants, while stuttering causes disruptions in speech flow. Phonological error analysis helps to understand the patterns of sound production errors and design interventions to improve speaking abilities. This research is essential for identifying phonological disorders and developing effective therapy methods. The study titled "Phonological Disorders in Mustofa in the Wkwk Project Podcast by Genflik" aims to gain a deeper understanding of phonological disorders in individuals with cleft lip and stuttering, and to find solutions to improve their communication abilities.